1994
DOI: 10.1080/00288233.1994.9513074
|View full text |Cite
|
Sign up to set email alerts
|

Improving the grazing and drought tolerance of temperate perennial grasses

Abstract: The improvement of grazing and drought tolerance of temperate (C3) perennial pasture grasses is an important component of plant improvement programmes. The improvement of these characteristics in grasses is best based on an understanding of the physiology of grass growth and development. This paper discusses the components of growth, i.e. buds, leaves, tillers, stems, and plants, how they interact, and how compensation between components occurs. These components are considered in relation to what is known abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 47 publications
2
34
0
1
Order By: Relevance
“…In addition, the grazing-tolerance and deep-rooting habit of these grasses are likely to have contributed to their superior recovery and tolerance of drought stress. These species can also become dormant under stresses of low soil moisture and high temperature (Kemp and Culvenor 1994;Watson et al 2001), while the good summer growth of Festuca arundinacea allows it to compete well with warmseason C 4 grasses (Oram and Lodge 2003). The short-term persistence of the so-called 'high performance' pastures based on Lolium multiflorum, commonly promoted by commercial firms in the region, was to be expected; it is likely that the relatively dry conditions experienced hastened the demise of this species, which was sown in only two paddocks of Farmlet A.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the grazing-tolerance and deep-rooting habit of these grasses are likely to have contributed to their superior recovery and tolerance of drought stress. These species can also become dormant under stresses of low soil moisture and high temperature (Kemp and Culvenor 1994;Watson et al 2001), while the good summer growth of Festuca arundinacea allows it to compete well with warmseason C 4 grasses (Oram and Lodge 2003). The short-term persistence of the so-called 'high performance' pastures based on Lolium multiflorum, commonly promoted by commercial firms in the region, was to be expected; it is likely that the relatively dry conditions experienced hastened the demise of this species, which was sown in only two paddocks of Farmlet A.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the notion that small seed size may aid persistence in annual communities (Carter 1987) may have little relevance in perennial communities where competition during early growth may be critical. Kemp & Culvenor (1994) have also promoted the evaluation of phalaris in mixtures to avoid selecting lines which exclude legumes by forming dense swards. There is a need to adopt a new methodology for selecting legumes for lowinput systems, one which takes account of the various systems in which they will be grown.…”
Section: Competition and Legume Evaluationmentioning
confidence: 99%
“…There has been little research on roots of NZ perennial ryegrasses, but interest in root systems is increasing because of their importance in drought tolerance (Kemp & Culvenor 1994), nitrate uptake (Nichols & Crush 2007) and the carbon balance of pastoral soils (Ghani et al 2010). Houlbrooke et al (1997) compared the cultivar Yatsyn and two breeding lines in a glasshouse experiment and showed that root growth of Yatsyn ryegrass was less sensitive than two ryegrass breeding lines to increased soil bulk density.…”
Section: Introductionmentioning
confidence: 99%